Woody Allen cineasta-historiador: ironia e identidade judaica em filmes sobre o período entreguerras - Ribeiro, Roberta do Carmo (2014)
Thinking about Woody Allen as "historian movie maker" will be the central idea and core theme of this research. We will examine how Woody Allen "writes" the History of the United States during the interwar period in some of his works, starting with his personal education as an American Jew and artist concerned about the question of the Jewish identity. We will present the main features of his cinematographic language, that is, using satire and ironic language in order to discuss with the audience. We will provide a synthesis of Allen's official biografy, as well as a presentation of his public image, charting a parallelism among these elements and some episodes from his autobiografical movie Radio Days (1987). The relation between History and Cinema will be highlighted too, starting with the concept of the "Movie maker - historian", as defined by the theorist Robert A. Rosenstone, looking for its exemplification in Woody Allen's works. We will analyze Zelig (1983) as a case of study, a fake documentary that reflects on the History of the Jews in America. We will also examine irony as a language, in the light of the Jewish tradition of humor and of Hayden White's historical theory of fiction. Under these premises, we will analyze The Purple Rose of Cairo (1985), which shows in its background the United States during the Great Depression, and Midnight in Paris (2011), which provides a critique to the glorification of past times. In all these movies, chosen for dealing with the interwar period and for using irony as a language, we will examine historical aspects and contributions to the Jewish identity in Allen's production.